Aplicação de argila branca comercial pura e modificada para adsorção de sulfeto de hidrogênio - Batista, Luiz Carlos Domingos (2012)
In this work were synthesized matrix-based commercial white clay in its composition having large amounts of kaolinite and quartz, with a certain percentage of iron oxide for use as an adsorbent for hydrogen sulfide (H2S). To characterize the effect of initial matrix techniques were used to characterize XRD, FTIR, XRF and TG. The initial clay mineral matrix was placed in contact with 0.1 molar solutions of the salts of Co2+, Ni2+, Cr3+ and a solution 0.1 g / 100ml rhodamine B. During the synthesis process, the solutions were placed in contact with the initial matrix for a period of 48 hours in order to have ion exchange with the clay mineral. To check the amount of exchanged metals, we used the technique of X-ray Fluorescence (XRF). After synthesis was initiated the process of adsorption of H2S, where the arrays were placed in the reactor, then by passing a stream of hydrogen sulfide. The matrix along with the reactor was weighed before and after to measure the amount of gas adsorbed. Based on the gravimetric data the matrix which had the highest performance of the adsorption matrix was exchanged with Ni2+ ions, obtaining a result of 11.13 mg H2S / g matrix, then the matrix coated with rhodamine B which was reached 10.13 mg H2S / g matrix